Identifikasi Tantangan dalam Mewujudkan Kesetaraan Hak Asasi Manusia bagi Penyadang Disabilitas Psikososial di Nepal - Bidya Maharjan (Badan Strategi Kebijakan Hukum, 2024)
Nepal is currently facing a severe mental health crisis characterized by a significant prevalence of mental illness that remains largely unaddressed. The issue is exacerbated by pervasive social stigma, lack of awareness, and insufficient political commitment, pushing mental health to the bottom of the political agenda. In Nepal, mental health treatment predominantly focuses on biomedical interventions, mainly ignoring the human rights aspects, highlighting the crucial need for a paradigm shift in approach. The enactment of the Convention on the Rights of Persons with Disabilities (CRPD) on June 6, 2010, presents an opportunity for a transformative shift in Nepal's approach to mental health. This research investigates the barriers within Nepal's rights-based mental health framework, drawing insights from individuals with psychosocial disabilities, their families, policymakers, legal experts, and NGO representatives. It features four case studies that highlight the challenges these individuals face, and the roles played by their families and communities in providing care. The objective is to provide insights into the daily realities of community members in Nepal. In summary, the study highlights the importance of adopting a robust human rights-based approach to quality practice. Such an approach, which fosters trust in engaging individuals with psychosocial disabilities, their families, the community, and mental health service providers, is not merely a theoretical concept but a vital requirement for enhancing mental health practices in Nepal.